Try the rabbit: a practical guide - Opoku Adjare, Stephen (Technical Centre for Agricultural and Rural Cooperation, 1990)
Based on experiences in a small-scale African smallholding, this manual describes the steps involved in raising rabbits, from constructing hutches to breeding and nutrition. The names of suitable greens abundantly available in West Africa are listed.